Survival Analysis of Stroke Incidence in National Health Insurance Participants from 2015–2020 - Irfan Ilmi; Lenny Suardi (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2025)
This study aims to analyze the survival of stroke patients enrolled in the National Health Insurance (Jaminan Kesehatan Nasional, JKN) program and factors affecting it during the 2015–2020 period. Survival analysis was utilized using the Kaplan-Meier estimator and the Cox Proportional Hazards model. The dataset consisted of 12,773 stroke patients sampled from BPJS Kesehatan administrative records. The results indicate that since being registered as BPJS Kesehatan participants or from the baseline year 2015, stroke patients had an average survival time of 2,264 days, with a 95% confidence interval between 2,240 and 2,287 days. The Cox model revealed that patients aged 18–35, 36–50, 51–65, and >65 had Hazard Ratios (HR) of 1.30, 1.69, 2.47, and 3.52, respectively. Female patients exhibited a lower risk of death (HR = 0.81) than males. Employment segment effects were modest, and regional disparities were observed, with the Eastern region showing a higher risk (HR = 1.29). Comorbidities further increased hazards, with hypertension (HR = 1.70) and diabetes (HR = 2.17) significantly raising mortality risk. As one of the first large-scale survival analyses using JKN national data, this study offers novel evidence on key determinants of stroke outcomes in Indonesia. Its findings highlight critical risk factors and support more targeted, data-driven strategies for stroke prevention under universal health coverage. Keywords: Cox Proportional Hazard; Kaplan-Meier; National Health Insurance Agency; Stroke; Survival Analysis.   Abstrak Penelitian ini bertujuan untuk menganalisis survival pasien stroke yang terdaftar dalam program Jaminan Kesehatan Nasional (JKN) dan faktor-faktor yang memengaruhinya selama periode 2015–2020. Metode yang digunakan adalah analisis survival dengan pendekatan Kaplan-Meier dan model Cox Proportional Hazards. Data yang dianalisis diambil dari sampel BPJS Kesehatan peserta JKN selama 2015–2020, yang berjumlah 12.773 pasien. Hasil penelitian menunjukkan bahwa sejak terdaftar sebagai peserta BPJS Kesehatan atau sejak tahun dasar 2015, pasien stroke memiliki waktu survival rata-rata 2.264 hari, dengan interval kepercayaan 95% antara 2.240 dan 2.287 hari. Model Cox mengungkapkan pasien berusia 18–35, 36–50, 51–65, dan >65 memiliki HR masing-masing sebesar 1,30, 1,69, 2,47, dan 3,52. Perempuan memiliki risiko lebih rendah (HR = 0,81) dibandingkan laki-laki. Efek pada segmen pekerjaan relatif kecil, dan disparitas regional teramati, dengan wilayah Timur menunjukkan risiko yang lebih tinggi (HR = 1,29). Komorbiditas semakin meningkatkan risiko, dengan hipertensi (HR = 1,70) dan diabetes (HR = 2,17) secara signifikan meningkatkan risiko mortalitas. Sebagai salah satu analisis survival skala besar pertama yang menggunakan data nasional JKN, studi ini menawarkan bukti baru tentang determinan utama luaran stroke di Indonesia. Temuannya menyoroti faktor risiko kritis dan mendukung strategi pencegahan stroke yang lebih terarah dan berbasis data dalam kerangka jaminan kesehatan semesta. Kata Kunci: Cox Proportional Hazard; Kaplan-Meier; Jaminan Kesehatan Nasional; Stroke; Analisis survival. 2020MSC: 91G05.